Impact of number of [18F]fluorodeoxyglucose‐PET‐positive lymph nodes on survival of patients receiving neoadjuvant chemotherapy and surgery for oesophageal cancer. Issue 1 (27th October 2015) - Miyata, H.; Yamasaki, M.; Makino, T.; Tatsumi, M.; Miyazaki, Y.; Takahashi, T.; Kurokawa, Y.; Takiguchi, S.; Mori, M.; Doki, Y.
Abstract : Background: [ 18 F]fluorodeoxyglucose (FDG)‐PET has been used to evaluate the response of primary tumours to neoadjuvant therapy for oesophageal cancer. The clinical significance of the number of PET‐positive nodes before and after therapy has not been investigated previously. Methods: [ 18 F] FDG‐ PET was performed before and 2–3 weeks after completion of neoadjuvant chemotherapy to identify the number of PET‐positive nodes, and these numbers were assessed in relation to metabolic changes in the primary tumour. Results: Of 302 patients in total, 90 had no PET‐positive nodes, 83 had one, 59 had two and 70 patients had three or more positive nodes before therapy. After treatment, the numbers were: none in 207 patients, one in 59, two in 20 and three or more in 16 patients. The number of PET‐positive nodes after treatment was influenced by both the number of PET‐positive nodes before therapy and the response to preoperative therapy, and correlated with the number of metastatic lymph nodes. Overall survival was longer in patients who had no PET‐positive nodes after treatment than in those who had one or more. Multivariable analysis identified the numbers of PET‐positive nodes before and after chemotherapy as independent prognostic factors, together with clinical response, tumour depth and lymph node involvement. Conclusion: The number of PET‐positive nodes after treatment correlated with survival in patients with oesophageal cancer who underwent neoadjuvant chemotherapy. Abstract : Dismal prognosis if PET‐positive nodes exist after treatment